APLIKASI PSIKOLOGI PENDIDIKAN ISLAM DI SEKOLAH - Diana Kurniati Kartika; Yuliana Intan Lestari; Vivik Shofiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Holistic education is a demand of the times amidst the complexity of global challenges, especially in forming a generation that is intellectually, morally, socially, and spiritually qualified. Islamic educational psychology is present as an approach that integrates the principles of psychology with the values ​​of Islamic teachings. This study aims to analyze the application of Islamic educational psychology in schools. The method used is a literature study with content analysis techniques. The results of the study indicate that Islamic educational psychology emphasizes the balance between cognitive, affective, social, and spiritual aspects in the learning process, based on the values ​​of monotheism, sincerity, patience, gratitude, and tawakal. Its application in schools involves the formation of a conducive learning environment, learning methods that are in accordance with the development of students, and comprehensive evaluation.